ANALISIS SOAL UAS GASAL 2017/2018 PKN KELAS VI SD DI UPTD PENDIDIKAN GENUK SEMARANG - Afandi, Muhamad; Nazilah, Itsna Iin (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2018)
The purpose of this research is to find out the quality of the exam questions of UAS Gasal 2017-2018 PKn Class VI Elementary School in the Genuk Semarang Education UPTD based on, among others: validity, reliability, level of difficulty, distinguishing power, and deceptive analysis. The results of the study are valid (76%) and invalid (24%) means that the odd UAS given to students can measure the ability of students, reliability there are numbers 1 to 50 coefficients of 0.48 which are criteria enough to mean the odd UAS questions given to participants students can measure the ability of students, difficulties are (54%) criteria are being and (28%) easy criteria means that the problem of odd UAS cannot memdakan ability of students with high and low ability as well as measuring the ability of students, the distinguishing ability is (52%) the criteria are enough that the odd UAS questions given to students can measure students' abilities, and there are (98%) misleading analysis which is not good, meaning that the repetition of the exam on the odd semester is not good enough. the criteria that have been obtained data processing of students' learning outcomes can be known criteria of validity, reliability, level of difficulty, distinguishing power, and deception analysis